The self-defense forces and postwar politics in Japan - Sadō, Akihiro (Japan Publishing Industry Foundation for Culture, 2017)
This book traces the inside story of U.S.-Japan relations and Japan's defense policy. It attempts to shine a light on the true state of the JSDF in the midst of new challenges that put it at a crossroads, including post-9/11 international terrorism, North Korean nuclear development, and China's increased military presence in Asia.